2015
DOI: 10.1117/12.2190212
|View full text |Cite
|
Sign up to set email alerts
|

Using the Stark effect to understand charge generation in organic solar cells

Abstract: We have used a femtosecond-resolved spectroscopic technique based on the Stark effect (electromodulated differential absorption) in order to investigate free charge generation and charge drift in solar cell devices of neat conjugated polymer pBTTT and in its 1:1 (by weight) blend with PCBM. In the latter, the fullerene molecules intercalate between the polymer side-chains, yielding a co-crystal phase. Our results show that free charge generation in both materials is ultrafast and strongly dependent on the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Importantly, these molecules must lie at or near the interface between n-and p-type semiconductors. The observed EA signal resembles the first derivative of the absorption spectra of these molecules (see more details in the SI, Section S4), as reported in the literature on TA measurements 11,29,30 and steady-state EA experiments 31 . Integrating this over photon energy gives the ground state absorption spectra of these molecules.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Importantly, these molecules must lie at or near the interface between n-and p-type semiconductors. The observed EA signal resembles the first derivative of the absorption spectra of these molecules (see more details in the SI, Section S4), as reported in the literature on TA measurements 11,29,30 and steady-state EA experiments 31 . Integrating this over photon energy gives the ground state absorption spectra of these molecules.…”
supporting
confidence: 77%
“…As illustrated in Figure 1 This EA signal has been used to create powerful pump-probe methods to investigate the interfaces of inorganic and organic material systems. 11,[28][29][30] Recently, we have demonstrated that this EA can be tracked as a function of time at BHJ interfaces. As the e-h pair separates across the interface, the electric field associated with it varies, giving rise to a time-dependent electric field and hence a time-dependent Stark shift and EA signal.…”
mentioning
confidence: 99%
“…The set-ups for femtosecond TA and EDA spectroscopy were closely related and based on a pump–probe scheme that we have previously described 25 59 . In brief, we used an amplified Ti:sapphire laser system (CPA-2001, Clark-MXR) with a 1 kHz repetition rate and output wavelength of 780 nm.…”
Section: Methodsmentioning
confidence: 99%